2002
DOI: 10.1001/archneur.59.7.1168
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Magnetic Resonance Imaging Study of Left Hemisphere Language Dominance in Children

Abstract: Hemispheric lateralization was clearly demonstrated in 8 children. As in adults, left hemisphere lateralization of receptive language is present at age 8 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
41
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 51 publications
11
41
1
4
Order By: Relevance
“…In the youngest readers, activity in the left posterior superior temporal sulcus was associated with the maturation of their phonological processing abilities, results that extend previous evidence that posterior language areas mature earlier than anterior ones (Balsamo et al, 2002;Simos et al, 2001). The developmental decrease in the right ventral stream activity indicates a decreasing reliance on nonlexical form recognition systems for word identification, and provides strong support for Orton's theory (1937) that learning to read requires children to disengage posterior right hemisphere visual representations that interfere with proper word identification.…”
Section: Plasticity Induced By Specific Training and Activitiessupporting
confidence: 84%
“…In the youngest readers, activity in the left posterior superior temporal sulcus was associated with the maturation of their phonological processing abilities, results that extend previous evidence that posterior language areas mature earlier than anterior ones (Balsamo et al, 2002;Simos et al, 2001). The developmental decrease in the right ventral stream activity indicates a decreasing reliance on nonlexical form recognition systems for word identification, and provides strong support for Orton's theory (1937) that learning to read requires children to disengage posterior right hemisphere visual representations that interfere with proper word identification.…”
Section: Plasticity Induced By Specific Training and Activitiessupporting
confidence: 84%
“…Recent evidence has suggested that, in children as in adults, cortical activity during semantic processing tends to be left lateralized (Balsamo et al, 2002;Balsamo, Xu & Gaillard, 2006;Binder, Desai, Graves & Conant, 2009;Binder et al, 1997). Though evidence shows that language networks for semantic processing are less specialized in children (Brauer & Frederici, 2007), one region that has been implicated in semantic processing both in children and adults is the fusiform gyrus, in the ventral temporal lobe.…”
Section: Fusiform Gyrus and Visual-perceptual Feature Processingmentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) studies have demonstrated that left hemisphere dominance of language function may already be present in infants Ͻ1 year old (Dehaene-Lambertz et al, 2002;Peña et al, 2003). In older children (Ͼ5 years old), not only left-lateralized responses during language-related tasks (Balsamo et al, 2002;Ahmad et al, 2003), but also correlations between brain functional lateralization and language performance (Everts et al, 2009) have been reported. Previous fMRI studies, however, did not concentrate on the link between language performance and brain functional lateralization in healthy preschool children aged 1-4 years old, because this is a challenging age for brain imaging methods such as fMRI.…”
Section: Introductionmentioning
confidence: 99%